2005
DOI: 10.1152/ajpcell.00193.2005
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle adherens junctions associated proteins are stable at the cell periphery during relaxation and activation

Abstract: This study was performed to determine the stability of the adherens junction (AJ)-associated proteins at the smooth muscle cell (SMC) plasma membrane during relaxing and activating conditions. Dog stomach, ileum, colon, and trachea tissues were stored in Ca2+-free PSS or regular PSS or were activated in 10 muM carbachol in PSS before rapid freezing. The tissues were subsequently sectioned and immunoreacted using antibodies for vinculin, talin, fibronectin, and caveolin to determine their cellular distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…In a previous study (16) we reported that AJ-associated proteins remain localized near the SMC periphery in tissues incubated in Ca 2ϩ -depleted PSS or PSS and with CCh activation. However, this work was done on untethered tissues, and thus it was not possible to confirm the contractile status of the tissue.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In a previous study (16) we reported that AJ-associated proteins remain localized near the SMC periphery in tissues incubated in Ca 2ϩ -depleted PSS or PSS and with CCh activation. However, this work was done on untethered tissues, and thus it was not possible to confirm the contractile status of the tissue.…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, we (16) have reported that the AJ-associated proteins vinculin, talin, and fibronectin are stably localized near the membrane of SMCs in gastrointestinal organs under relaxed and activated conditions, suggesting that these proteins are very stable at the cell periphery in intact organs. However, many laboratories (including our own) use enzymatic treatment of SM tissue to isolate SMCs for a wide range of in vitro and cell culture experiments.…”
mentioning
confidence: 62%
“…Vinculin binds directly to actin filaments and anchors them to transmembrane integrin proteins indirectly through its binding to talin and ␣-actinin, which are integrin-binding proteins that can also bind directly to filamentous actin (14 -19). Although vinculin has traditionally been viewed as a stable constituent of adhesion junctions in smooth muscle tissues (20,21), it is widely recognized to play a dynamic role in the growth and maturation of adhesion junctions during cell migration and traction in substrate adherent cells (22). Our studies have shown that vinculin plays an active role in tension generation in airway smooth muscle tissues during active contraction (10,23).…”
mentioning
confidence: 74%
“…Talin is a cytoskeletal focal adhesion protein on the cytosolic side of the membrane, and fibronectin is an extracellular glycoprotein (20,21). When considered together, expression of these contractile and focal adhesion proteins provides an additional indicator of SM differentiation beyond previous studies, which observed only SM ␣-actin or SM myosin.…”
mentioning
confidence: 99%